2021
DOI: 10.3389/fpls.2021.710139
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Application Modulates the Growth, Rhizosphere Soil Characteristics, and Bacterial Community Structure in Sugarcane

Abstract: Silicon (Si) deficiency, caused by acidic soil and rainy climate, is a major constraint for sugarcane production in southern China. Si application generally improves sugarcane growth; however, there are few studies on the relationships between enhanced plant growth, changes in rhizosphere soil, and bacterial communities. A field experiment was conducted to measure sugarcane agronomic traits, plant nutrient contents, rhizosphere soil enzyme activities and chemical properties, and the rhizosphere bacterial commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Generally, Si can influence the soil microbial community in the rhizosphere soil microenvironment in three main ways. The first is by directly modulating the microbial growth [ 17 ]; the second is by recognizing that Si can change soil microbial habitats by modifying soil physiochemical properties and enzymes; and the third is by recognizing that Si can induce the establishment of new advantaged microbial communities by altering rhizosphere soil metabolites [ 25 , 26 , 48 , 49 ]. Similarly, the findings of the present study suggested remarkable differences in the diversity and structure of the rhizosphere soil bacterial community in RS and RSSI treatments ( Table S1 , Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, Si can influence the soil microbial community in the rhizosphere soil microenvironment in three main ways. The first is by directly modulating the microbial growth [ 17 ]; the second is by recognizing that Si can change soil microbial habitats by modifying soil physiochemical properties and enzymes; and the third is by recognizing that Si can induce the establishment of new advantaged microbial communities by altering rhizosphere soil metabolites [ 25 , 26 , 48 , 49 ]. Similarly, the findings of the present study suggested remarkable differences in the diversity and structure of the rhizosphere soil bacterial community in RS and RSSI treatments ( Table S1 , Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pot experiment was conducted in a randomized block design by using four Si fertilizer treatments including controls: (i) CK treatment—plants were irrigated by ultrapure water without soluble Si, and not inoculated with R. solanacearum ; (ii) SI treatment—plants were irrigated with a 3 mM sodium silicate solution, but not inoculated with R. solanacearum ; (iii) RS treatment—plants were irrigated with ultrapure water without soluble Si, but inoculated with R. solanacearum ; (iv) RSSI treatment—plants were irrigated with a 3 mM sodium silicate solution and inoculated with R. solanacearum [ 48 ]. Each treatment was performed in quintuplicate with 12 plants in each replication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that the bacterial and archaeal community diversity and composition in three types of soil were influenced by eight soil geochemical properties: pH, moisture content, and total carbon are important properties of soils; nitrate, nitrite, ammonium, and phosphate are often limiting nutrients in poor nutrition areas; and silicate is a ubiquitous nutrient and can also affect microbial communities when added to soil as fertilizer [ 29 ]. The competing hypothesis is that not all of these eight soil geochemical properties play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Solid soil particles, including nanosized minerals, can also infl uence bacteria's enzymatic activity [6]. In addition, many preparations for crop production contain various minerals, for example, bentonite, vermiculite, and silica [6][7][8] . Th e infl uence of abiotic factors on B. subtilis IMV B-7023 phytase activity has not previously been studied, so this was the aim of this research.…”
mentioning
confidence: 99%